Pengaruh Kredibilitas Endorser Lokal terhadap Iklan Suplemen dan Minat Beli Konsumen pada New Normal - Fadli Fadli; Argnina Kurnia Sandi (Jurnal Health Sains, 2021)
The Credibility of the Local Endorser is a person who comes from the locale where the advertising media is present the greater the acceptance level of the endorser's credibility the more likely the receiver will receive the advertisement. Purchase interest is something that is obtained from a series of thought processes that form a perception that includes needs recognition information search until finally buying interest arises. When the public is willing to accept the product advertisement offered there is a possibility that there will be an interest in buying the product. The purpose of this study was to determine whether there is an effect of local endorser's credibility on supplement advertising and to determine whether there is an effect of local endorser's credibility on consumer buying interest in New Normal. In this study, the authors used a quantitative approach. The population in this study were 11th-grade high school students of the 20192020 class aged 15-20 years who were studying at SMA Negeri 1 Sungai Raya Kepulauan. The sample collection techniques used were Probability Sampling and Nonprobability Sampling with 92 respondents. This research method is a survey method using data from a questionnaire. The results showed that the significance value of Variable X was 0.289. The Y variable is 0.357 and the Y variable is 0.146 from 0.05 and the account value is 12.069 0.361. The conclusion of this study is that there is a significant positive relationship between the Credibility of Local Endorsers on Supplementary Ads and Credibility of Local Endorsers on Consumer Purchase Intention at New Normal.